2009
DOI: 10.1080/14756360802218763
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human poly(A)-specific ribonuclease (PARN) by purine nucleotides: kinetic analysis

Abstract: Poly(A)-specific ribonuclease (PARN) is a cap-interacting and poly(A)-specific 30 -exoribonuclease that efficiently degrades mRNA poly(A) tails. Based on the enzyme's preference for its natural substrates, we examined the role of purine nucleotides as potent effectors of human PARN activity. We found that all purine nucleotides tested can reduce poly(A) degradation by PARN. Detailed kinetic analysis revealed that RTP nucleotides behave as non-competitive inhibitors while RDP and RMP exhibit competitive inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…Considering that PARN is an allosteric enzyme [ 29 ], it is important to find that the Mg 2+ coordination could induce conformational changes in the other domains of PARN, which might contribute to the allosteric regulation of PARN. This conclusion is quite consistent with the previous observations by Balatsos et al ., which showed that the coordination of Mg 2+ could release the non-competitive nucleotide inhibitors of PARN [ 30 ]. Our findings is also consistent with that previously observed by Dupureur and Dominguez, which showed that the mutations in the active site of Pvu II endonuclease resulted in significant changes in the conformation and stability of the enzyme [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering that PARN is an allosteric enzyme [ 29 ], it is important to find that the Mg 2+ coordination could induce conformational changes in the other domains of PARN, which might contribute to the allosteric regulation of PARN. This conclusion is quite consistent with the previous observations by Balatsos et al ., which showed that the coordination of Mg 2+ could release the non-competitive nucleotide inhibitors of PARN [ 30 ]. Our findings is also consistent with that previously observed by Dupureur and Dominguez, which showed that the mutations in the active site of Pvu II endonuclease resulted in significant changes in the conformation and stability of the enzyme [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The enzymatic activity of recombinant AtHESP was determined by a colorimetric assay as described with some modifications. [24][25][26] Briefly, the reactions were performed with 0.1-0.15 nM recombinant AtHESP in 1 ml reactions. The absorbance of poly(A), poly(U), poly(C) or poly(G) (all from Sigma-Aldrich) was measured at appropriate wavelengths [poly(A), 662 nm; poly(U), 663 nm; poly(G), 665 nm; poly(C), 667 nm].…”
Section: Methodsmentioning
confidence: 99%
“…Methylene blue buffer was prepared by dissolving 1. (19). The final reaction volume was 100 μL, and the reaction was performed at 30°C for 5-10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been shown that natural purine nucleotides also inhibit PARN activity (18,19). More specifically, we have shown previously that RTP nucleotides inhibit the enzyme noncompetitively, while RDP and RMP act in a competitive manner (19).…”
mentioning
confidence: 96%
See 1 more Smart Citation